(untitled) (Huellas, 2023)
Greater San Miguel de Tucumán (GSMT) is an intermediate city in the province of Tucumán, which is fragmented, with informal settlements that are affected by exclusion, stigmatization and marginalization. This context deepens their conditions of vulnerability and prevents them from participating in the processes of production of the hegemonic discourses that circulate throughout them. Thus, this paper aims at analyzing the symbolic boundaries that constitute a key role to understand the modalities operating when setting and sustaining inequality conditions, paying as much attention as when analyzing material aspects. To this end, the Diagonal Norte neighborhood is taken as a case study, which is considered a slum located in the municipality of Yerba Buena, where private neighborhoods are mostly placed. On the one hand, the purpose is to system-atize and analyze news publications where the neighborhood is mentioned and, on the other hand, to carry out interviews to neighbors. The data obtained allow us to point out different modalities in the construction of social representations about the neighborhood and the circulation of different discourses, according to the relationship they have with the logics of sustaining or transforming inequality conditions